Evaluation the efficiency of Trichomonas vaginalis depending on clinical sings , direct examination ,culturing and serological test (Baghdad Science Journal, 2011)
The adequacy of diagnostic tests, together with trichomoniasis associated clinical symptoms, were investigated in females suffering vaginitis, and they were referred to the Gynecology Department, Al-Yarmouk Teaching Hospital during the period December 2004 – June 2005. The total number of patients was 250 cases (age range: 18 - 52 years), and each patient was examined using a sterile speculum to obtain vaginal swabs for examination. The diagnosis with T. vaginalis was done in many methods. The direct methods included wet and stained (Leishman's stain) examinations and cultivation in different culture media (Kupferberg Trichomonas Broth Base;, Trichomonas Agar Base; TAB and Trichomonas Modified CPLM), while the indirect methods were serological detections of anti-trichomonas antibodies in the sera of patients by using of indirect haemagglutination test (IHAT) and enzyme linked immunosorbent assay (ELISA). The results of this profile were as the following:1. Out of 250 females with abnormal vaginal discharges, 15 patients (6%) were infected with T. vaginalis.2. The sensitivity of testing methods was different. It was 66.7 and 13.3% for wet and stained examinations, respectively. In culture examinations, the sensitivity was 60, 80 and 100% for Kupferberg, TAB and CPLM media, respectively, while the sensitivity IHAT and ELISA were 40 and 73.3%, respectively.3. The clinical sings of infection in women were discharge and itching (46.7%), discharge with itching and dysuria (20.0%), discharge only (13.3%), itching only (13.3%) and discharge with dysuria (6.7%).Therefore we can conclude that impossible to the clinical signs in diagnose of Trichomonasis because of the variation and the laboratory diagnosis is necessary especially the cultivation method.